Cutaneous tuberculosis—ambiguous transmission, bacterial diversity with biofilm formation in humoral abnormality: case report illustration - Zdziarski, Przemysław; Paściak, Mariola; Chudzik, Anna; Kozińska, Monika; Augustynowicz-Kopeć, Ewa; Gamian, Andrzej (Frontiers in Public Health, 2023)
Cutaneous tuberculosis (CTB) and its paucibacillary forms, is rare and difficult to diagnose, especially in immunocompromised patients with significant comorbidity. The sensitivity of some of the traditional tests is low in paucibacillary lesions and it is difficult to distinguish between M. tuberculosis and other mycobacterial species or acid-fast bacteria in skin biopsies based on morphology. The aim of the work was introduction of the modern concept of microbiome and diagnostic chain into clinical practice (patient–centerd care) with presentation of atypical form of cutaneous tuberculosis with necrotizing nonhealing ulcers leading to polymicrobial infection. The immunocompromised patient with humoral abnormality (plasma cell dyscrasia) and severe paraproteinemia developed multiorgan tuberculosis. Although cutaneous manifestation preceded systemic and pulmonary symptoms (approximately half a year), the mycobacterial genotyping confirmed the same MTB strain existence in skin ulcers, and respiratory system. Therefore the infectious chain: transmission, portal of entry and bacterial spreading in vivo were unclear. Microbial diversity found in wound microbiota (among others Gordonia bronchialis, Corynebacterium tuberculostearicum, Staphylococcus haemolyticus, and Pseudomonas oryzihabitans) was associated with spread of the skin lesion. The in-vitro biofilm forming capacity of strains isolated from the wound may represent the potential virulence of these strains. Thus, the role of polymicrobial biofilm may be crucial in ulcer formation and CTB manifestation. Severe wound healing as a unique biofilm-forming niche should be tested for Mycobacterium (on species and strain level) and coexisting microorganisms using a wide range of microbiological techniques. In immunodeficient patients with non-typical CTB presentation the chain of transmission and MTB spread is still an open issue for further research.